Effect of Enhanced Antimicrobial Fish Gelatin and Lactic Acid Coating on the Shelf Life of Fresh and Previously Frozen Shrimp - Hunter Songy; Katheryn Parraga; Wenqing Xu; Evelyn Watts (Fishes)
Gelatin coatings have been shown to successfully slow the oxidation of fresh foods. Furthermore, organic acids have proven effective in the inhibition of bacteria and the extension of product shelf life. The purpose of this study was to observe the effects of gelatin and lactic acid treatment combinations on fresh and previously frozen (thawed) wild-caught shrimp. The samples were separated into four treatment groups: control (C), gelatin coating (G), lactic acid followed by gelatin coating (L), and gelatin infused with lactic acid coating (LG). Half of each group was stored at refrigeration temperature (≤4 °C), while the other half was frozen (≤−18 °C) and thawed for the thawed study. Physical, chemical, and microbiological changes were observed in refrigeration storage for 8 days. Results showed that fresh and thawed shrimp exhibited darkening in color over time. Treatments with lactic acid were more blue than yellow. Treated samples developed less oxidation than the control. Psychrophilic counts for samples L and LG remained below the 7 log CFU/g threshold throughout the study. In fresh shrimp samples, the addition of just a gelatin coating was able to increase shelf life by three days, while the addition of lactic acid successfully lowered microbial counts and extended the shelf life by six days. The freeze–thaw cycle negatively affected the extension of shelf life in the G group.